Anti-allergic effect of 5,7-dihydroxy-4-methylcoumarin in IgE-mediated RBL-2H3 cells and PCA murine model - Sugeun Gwon; Seong-Ah Shin; Moonsu Kim; Sun Young Moon; Seyeon Choi; Minji Kim; Jun Hyuck Lee; Hyun Ho Park; Chang Sup Lee (Applied Biological Chemistry)
Abstract Allergy is an immune-mediated disorder characterized by an exaggerated response of the immune system to non-hazardous substances, resulting in allergic symptoms such as rash, itching, and runny nose. Current therapeutic interventions include antihistamines and steroids; however, they induce several side effects. Although 5,7-dihydroxy-4-methylcoumarin, a phytochemical derivative, has been demonstrated to exhibit antioxidant, anti-apoptotic, and anti-aggregatory effects, its anti-allergic properties and underlying molecular mechanisms remain elusive. Therefore, this study was conducted to investigate the anti-allergic effects of 5,7-dihydroxy-4-methylcoumarin in two experimental models: rat basophilic leukemia-2H3 cells sensitized using dinitrophenyl-specific immunoglobulin E (IgE)/human serum albumin and a passive cutaneous anaphylaxis (PCA) murine model. Our findings demonstrated that 5,7-dihydroxy-4-methylcoumarin reduced the release of histamine and β-hexosaminidase and downregulated the mRNA expression of allergic-inflammatory cytokines, such as interleukin (IL)-4, IL-13, and tumor necrosis factor-alpha, as well as the inflammatory enzyme cyclooxygenase-2. Furthermore, 5,7-dihydroxy-4-methylcoumarin reduced the phosphorylation of mitogen-activated protein kinases such as extracellular signal-regulated kinase and p38, as well as protein kinase B. In vivo, 5,7-dihydroxy-4-methylcoumarin reduced PCA reaction, as evidenced by reduced Evans blue dye extravasation in IgE-mediated local allergic responses. Collectively, these results suggest that 5,7-dihydroxy-4-methylcoumarin holds promise as a novel candidate for the development of anti-allergic drugs.